Sinemadan televizyona Türkiye'de 2000 sonrası televizyon belgeselciliği - Karademir, Hakan Kerim (My University, 2019)
Türkiye’de ve dünyada hareketli görüntü alanında 2000’lerden sonra çok hızlı birgelişmenin yaşandığı gözlenebilmektedir. Kuşkusuz bu gelişmeyi dijital yeniliklergetirdi. Bu yenilik belgesel film alanını da etkiledi. Etki belgesel filmin çekilmesi,kurgulanması, gösterilmesi alanlarında açık bir biçimde belirleyici oldu. Böyle bir konudaakademik çalışma yapılmasına da zaten 2000’lerde yaşanan bu değişim ve dönüşüm yolaçmıştır. Bu yenilikler sinema ve belgesel sinemanın dağıtım ve gösterim alanlarınınsınırlarını da hızla ortadan kaldırmıştır.Hem tüm dünyada hem de Türkiye gibi büyük bir hızla gelişmekte olan bir ülkedetelevizyon kanalları artmıştır. Film festivalleri belgesel filmlere geniş yer açmayabaşlamıştır. İzleyici kitleler, belgesel filmlere rağbet etmeye başlamıştır. Bu alanda yenigelişmelerin kapıları açmıştır. Türkiye Cumhuriyeti Kültür Bakanlığı, belgesel filmüretimine destek sağlama noktasında yoğun biçimde çalışmalar içine girmiştir. Belgeselfilmler Türkiye’de ve dünya ölçeğinde eğlenme, öğrenme, bilgi sahibi olma alanı halinegelmiştir. Bu tez çalışmasında bu gelişmeler derinine ele alınarak nedenler ve sonuçlarıüzerinde titizlikle durulmuş ve yepyeni bulgulara ulaşılmıştır.

It is observed that there has been a rapid advancement in the motion picture industryin Turkey and the world after 2000s. There is no doubt that such advancement wastriggered by digital innovations, which have also affected the documentary film industry.The effect has been a clear determinant in shooting, fictionalizing and screeningdocumentary films. As a matter of fact, such change and transformation experienced inthe 2000s have led to the conduct of an academic study on this subject. Such innovationshave also rapidly removed the borders of distribution and screening industries of cinemaand documentary cinema.The number of television channels has increased both in the world and in Turkey,which is a rapidly developing country. Film festivals have also started to featuredocumentary films. Audience has begun demanding documentary films. Doors have beenopened to new developments in this industry. Republic of Turkey Ministry of Culture hasbegun intensively working on supporting production of documentaries. Documentaryfilms have become a medium of entertainment, learning and information in Turkey andacross the world. This thesis has meticulously focused on causes and effects and arrivedat new findings by examining such developments thoroughly.
Keywords: belgesel; Belgesel televizyon programları; Documentary television programs; Fiction; Film; film Documentary; kurmaca; Mockumentary; mokümanter; Turkey; Türkiye